STUDI KORELASI KUALITAS SOAL UJIAN AKHIR SEMESTER MATA KULIAH BIOLOGI DASAR DENGAN PRESTASI BELAJAR MAHASISWA PROGRAM STUDI ILMU PENGETAHUAN ALAM FKIP UST SEMESTER GASAL TAHUN AJARAN 2010/2011 - Widowati Pusporini (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2014)
Testing of the student’s ability is required to know the success of the learning activity process. The purpose of the study is to describe the characteristic of the final term examination test quality of Basic Biology Course of Natural Science study Program FKIP UST on the odd term in Academic Year of 2010/2011 reviewed from the theorical and empirical aspect.he study aimed to determine the relationship of the final term examination test quality of basic Biology course. The process are blue print establishment, optional objective test determination, assessment criteria, examination, revision, and trial. The test characteristic clarified as follows: good content validity, content validity resulted through item examination by practitioners and experts.. The responses of the student are analyzed quantitavely to obtain the psychometric characteristic of the test. This study was carried out in the Natural Science Education Study Program FKIP UST Yogyakarta. The sample of research are 46 students of Natural Science Education Study Program FKIP UST attended the Basic Biology Course on the odd term in Academic Year of 2010/2011Result of the analysis using ITEMAN shows the test have alpha reliability coefficient 0,697 and SEM 2,488. The Analysis result using Iteman shows that this test instrument has a quite good item difficulty level, good item discrimination, and good distracter affectivity. Overall examination question is good, but still to be revised in determining the language distractor and construction so the testee can understand the question easily. Suggestions for this research are to be widely used, the test should not be carried out once, the samples should be taken from the wider scope. This examination should be supported with performance test to measure the real students ability.